Parameterization of the Hamiltonian Dielectric Solvent (HADES) Reaction‐Field Method for the Solvation Free Energies of Amino Acid Side‐Chain Analogs. Issue 8 (27th March 2015) - Zachmann, Martin; Mathias, Gerald; Antes, Iris
Abstract: Optimization of the Hamiltonian dielectric solvent (HADES) method for biomolecular simulations in a dielectric continuum is presented with the goal of calculating accurate absolute solvation free energies while retaining the model's accuracy in predicting conformational free‐energy differences. The solvation free energies of neutral and polar amino acid side‐chain analogs calculated by using HADES, which may optionally include nonpolar contributions, were optimized against experimental data to reach a chemical accuracy of about 0.5 kcal mol −1 . The new parameters were evaluated for charged side‐chain analogs. The HADES results were compared with explicit‐solvent, generalized Born, Poisson–Boltzmann, and QM‐based methods. The potentials of mean force (PMFs) between pairs of side‐chain analogs obtained by using HADES and explicit‐solvent simulations were used to evaluate the effects of the improved parameters optimized for solvation free energies on intermolecular potentials. Abstract : Molecular dynamics and modeling: Parameterization of the recently developed Hamiltonian dielectric continuum solvation model (HADES) is refined to give the solvation free energies of amino‐acid analogs within chemical accuracy. The figure shows the potential of mean force between two side‐chain analogs immersed in a dielectric continuum.